Effects of dexamethasone, ibuprofen, and ligustrazini on lipopolysaccharides-induced tumor necrosis factor alpha production - Qiu Hai-Bo; Pan Jia-Qi; Du Bin; Zhao Yong-Qiang; Chen De-Chang (Acta Pharmacologica Sinica, 2016)
AIM: To study the influence of dexamethasone (Dex), ibuprofen (Ibu), and ligustrazini (Lig) on lipopolysaccharides (LPS)-induced tumor necrosis factor alpha (TNF alpha) gene expression (both mRNA and protein). METHODS: TNF alpha in supernatants of human whole blood was measured by ELISA; The TNF alpha mRNA was assessed by slot blot analysis. RESULTS: LPS-induced TNF alpha production was in a dose-dependent manner. TNF alpha levels in the whole blood increased markedly at 3 h and peaked at 6 h. The induction of TNF alpha mRNA was very rapid, peaking at 2 h after LPS challenge. Dex exerted inhibitory effects on TNF alpha production in a dose-dependent manner. Ibu and Lig had 2-phase effects on TNF alpha release. CONCLUSION: Dex, Ibu, and Lig affected TNF alpha gene expression, so they may be new approaches of anti-TNF alpha for treatment of sepsis.